Effect of ketorolac administration post bone cavitation surgery on some hematological parameters - Omar, Raffal A. (The Iraqi Journal of Veterinary Medicine, 2017)
This study was designed to determine the effect of ketorolac on some hematological parameters post cavitation surgery in domestic rabbits. Ninety-six adult domestic local breed male rabbits were used in this study, weighing (1.23 ± 0.33) kg. They were divided randomly into two groups in the first one (n= 48/group) which represented control group, while the second one (n=48/group) represented the treated group (Ketorolac group). All rabbits in both groups undergoes surgical operation (bone cavitation in femur bone) under general anesthesia. In the Ketorolac group, animals were treated by using 30 mg/kg of Ketorolac directly post-operation and continued daily for 5 days, while in Control group no treatment was given postoperatively. The hematological parameters were recorded which include white blood cells count; red blood cells count; hemoglobin; packed cell volume; mean corpuscular hemoglobin and mean corpuscular hemoglobin concentration; mean corpuscular volume and platelets at the period of (3, 5, 7, 14, 21, 28, 35, and 42) days post operation were estimated. Results concerning hematological values showed no significant differences in packed cell volume values between control and treated group and within each group, while haemoglobin values showed a significant decrease at period 7 and 14 days between control and treated group. Within control group the significant decrease were noticed clearly at period of 7 days. Data concerning mean corpuscular hemoglobin values within control group showed significant decrease were noticed at 5 day, but within treated group, there were no significant differences. mean corpuscular hemoglobin concentration values showed significant decrease ate period 3; 5 and 21 days between control group and treated group respectively. Within control group the significant decrease were noticed obviously at 5 days while within treated group the significant decrease were noticed at 35 days. mean corpuscular volume values showed significant increase at 3 and 5 days period between control and treated groups. Platelets counts within control group showed significant increase at period of 14 days, within treated group the significant increase were recorded at 42 days. Red blood cells showed significant decrease between control and treated groups, while within control group, the significant decrease were at 7 days. White blood cells count within treated group showed significant increase recorded at 21 days. Differential White blood cells count concerning Lymphocytes cells within control group the significant increase were recorded at 42 days while the significant decrease were noticed at 21 days, but within treated group the significant increase were recorded at 35 days and significant decrease were noticed at 14 days. Neutrophils counts showed significant decrease at periods 3, 14, 28 and 42 days between control and treated groups respectively; while within control group there were significant decrease at 3 days, but within treated group the significant decrease were noticed at 42 days. Monocytes cells showed significant increase at 35 days between control and treated groups, within control group there were significant increase at 35 days, while within treated group the significant increase recorded at 7 days.